The Vicissitudes of the Edo State Council for Arts and Culture’s Performing Troupe from 1996 to 2016 - Daniel Omoruan (Selected Topics in Humanities and Social Sciences Vol. 1, 2021)
The ding-dong charade of Edo State Council for Arts and Culture Performing Troupe (ESCFAACPT) cannot be divorced from the vacillating condition the establishment had been experiencing since its establishment. This condition is fore-grounded, first, on the council’s association with a cacophony of nomenclature, and, second, on the mindset of the different governors who have ruled the state since its creation. Another topic of discussion would be the troupe’s accomplishments, as well as the calibre of artists it had bred and accommodated over the years. This study is based on performance studies and historicity, as proposed by Richard Schechner, and uses a historical-analytic method. It claims that successive governments have suppressed performance and creativity in the ESCFAACPT through neglect and disinterestedness since the mid-1990s. This has rendered the troupe ineffective, ineffectual, and incapable of adapting to modern arts and cultural administration, management, and performance techniques, which is a necessary tonic for its success and survival in contemporary performance.